Microstructure of Al-Si Slurry Coatings on Austenitic High-Temperature Creep Resisting Cast Steel - Agnieszka E. Kochmańska (Advances in Materials Science and Engineering)
This paper presents the results of microstructural examinations on slurry aluminide coatings using scanning electron microscopy, X-ray microanalysis, and X-ray diffraction. Aluminide coatings were produced in air atmosphere on austenitic high-temperature creep resisting cast steel. The function of aluminide coatings is the protection of the equipment components against the high-temperature corrosion in a carburising atmosphere under thermal shock conditions. The obtained coatings had a multilayered structure composed of intermetallic compounds. The composition of newly developed slurry was powders of aluminium and silicon; NaCl, KCl, and NaF halide salts; and a water solution of a soluble glass as an inorganic binder. The application of the inorganic binder in the slurry allowed to produce the coatings in one single step without additional annealing at an intermediate temperature as it is when applied organic binder. The coatings were formed on both: the ground surface and on the raw cast surface. The main technological parameters were temperature (732–1068°C) and time of annealing (3.3–11.7 h) and the Al/Si ratio (4–14) in the slurry. The rotatable design was used to evaluate the effect of the production parameters on the coatings thickness. The correlation between the technological parameters and the coating structure was determined.